Percutaneous endoscopic gastrostomy in the neurosurgical intensive care unit: Complications and outcome - (:unkn) unknown (AMER SOC PARENTERAL & ENTERAL NUTRITION, 2007)
Background: Even with a functioning gastrointestinal tract, it is not always easy to initiate oral feeding in some neurosurgical patients because of their persistently depressed neurologic status or severe lower cranial nerve palsies. Percutaneous endoscopic gastrostomy (PEG) may be required for long-term feeding in these patients. The purpose of the present study is to report our experience with PEG chosen for establishing an enteral route in patients of neurosurgical intensive care unit (ICU). Methods: The outcome and complications of PEG in neurosurgical ICU patients of Marmara University Institute of Neurological Science between January 2001 and November 2006 were retrospectively evaluated. Results: Thirty-one patients, with the median age of 51 years (range, 14-78 years) underwent PEG placement. PEG was placed before the craniotomy in 2 patients and after in 29. Indications for PEG were absent gag reflex in 10 patients and low Glasgow Coma Scale score in 2 1. Before the PEG tube insertion, 18 patients had enteral nutrition by a nasogastric tube and 10 had parenteral nutrition (PN), with a median duration of 14.5 (range, 4-60) and 12 (range, 7-25) days, respectively. Two patients accidentally pulled out the gastrostomy tubes 10 and 11 days after insertion. Buried bumper syndrome developed in 1 patient. Two patients died 8 and 34 days after the procedure in the neurosurgical ICU. Twenty-nine patients were discharged from the hospital while being fed via the PEG tubes. In 11 patients who were able to resume oral feeding, the tube was removed, with a median interval of 62 (range, 25-150) days. Procedure-related mortality, 30-day mortality, and overall mortality of the patients were 0%, 6.4%, and 45%, respectively. Conclusion: PEG is a safe and well-tolerated gastrostomy method for neurosurgical ICU patients with depressed neurologic state or severe lower cranial nerve palsies.
Keywords: VENTRICULOPERITONEAL SHUNT; TUBE PLACEMENT; MANAGEMENT; NUTRITION; RISK